The Effectiveness of OSTO-3P Machine in The Process of Making Hygienic Tempe - Suwito, Djoko; Purwidiani, Niken; Yunitasari, Bellina; Budijono, Agung Prijo; Umaroh, Susi Tri; Asmara, Yuli Panca (Proceeding of International Joint Conference on UNESA, 2024)
Tempe is a native Indonesian food, made from soybeans and widely consumed by the majority of Indonesian people. However, the tempe production process still uses conventional methods with makeshift tools, so the quality and cleanliness (hygiene) of the product is not maximized. The tempe production process, especially in the process of peeling, breaking and separating the soybean epidermis takes a long time and tiring and it is difficult for tempe producers to find employees to assist the production process. In dealing with this problem, the researchers found an innovative solution, namely the OSTO-3P Machine which features soybean cleaning, soybean splitting, and soybean separator with its epidermis. The method of implementing this activity is making detailed drawings, carrying out assembly manufacturing processes and machine trials, handover and machine implementation. Through the application of the OSTO-3P machine, it has a positive impact on the process of making tempe including: 1) increasing the production capacity of tempe to be doubled from before, 2) being able to speed up the process of splitting and separating soybeans which was originally 50kg/hour to 150kg/hour, 3) quality Tempe is more hygienic because it does not come into direct contact with hands and uses components made from foodgrade.